Modified sulfonic acid resin for removing gas phase inorganic fluorine and preparation method, application and filter thereof
Patent Information
- Application Number
- CN202611081860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]现有除氟吸附材料主要分为三类,均存在明显缺陷:活性炭、碱性浸渍滤料、分子筛:对氟化物选择性差,极易吸附水汽、酸性杂质,吸附容量低、穿透速度快,碱性浸渍材料易粉化产尘、有机挥发物释放量大,无法满足半导体高洁净要求;氨基螯合型 PS-DVB 双金属树脂:制备流程中氯甲醚、长链多胺残留严重,成品 TVOC 释放超标,氨基配体在高湿酸性气相环境易水解脱落,金属离子溶出风险高,且全部现有专利仅应用于水体液相除氟,无气相空气过滤配套工艺与过滤器结构设计;常规载锆吸附树脂:以单一树脂为载体,仅浸渍单金属氧化锆,存在三大缺陷:(1)无镧金属协同,低浓度气态氟选择性差、吸附容量低;(2)仅简单浸渍负载金属,无原位纳米共沉淀工艺,金属氧化物易脱落溶出;(3)全部现有磺酸载锆树脂专利限定污水处理液相工况,未针对 HF、SiF4气相水解特性设计亲水扩孔、低释气纯化、单层过滤器件配套工艺
[0020]本发明通过Zr4+和La3+的协同负载及原位共沉淀生成纳米水合锆镧固溶体,在树脂骨架上构建了高密度的氟离子特异性吸附位点。水合氧化锆(HZO)和水合氧化镧(HLO)对氟离子具有极强的配位亲和力,其除氟机制主要为配位体交换作用——氟离子取代金属氧化物/氢氧化物表面的羟基基团,形成稳定的内配位化合物。Zr-La双金属固溶体相较于单一金属氧化物具有更丰富的表面羟基和更强的氟离子结合能。经测试,本发明改性树脂对气相HF的饱和吸附容量可达20~40 mg/g,较未改性磺酸树脂提高5~10倍。Zr4+和La3+对氟离子的选择性配位作用使本发明树脂在HCl、SO2、NOx等共存酸性气体中仍能优先吸附HF,选择性系数(HF/HCl)≥5。
Smart Images

Figure CN122958618A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resin synthesis, specifically relating to a modified sulfonic acid resin for removing gaseous inorganic fluorine, its preparation method, application, and filter. Background Technology
[0002] With the continuous development of industrial production, the emission of fluorine-containing waste gas is constantly increasing, becoming a significant source of air pollution. Inorganic fluorides such as HF, SiF4, and NF3 are continuously generated during semiconductor manufacturing processes. These gases are highly corrosive and toxic; even trace amounts of fluorine residue can cause wafer surface defects and corrosion of precision cavities, while also polluting cleanroom environments. Therefore, gaseous fluorine pollutants must be controlled at the ppb level.
[0003] Existing fluoride removal adsorption materials are mainly divided into three categories, all of which have obvious defects: activated carbon, alkaline impregnated filter media, and molecular sieves: they have poor selectivity for fluorides, readily adsorb water vapor and acidic impurities, have low adsorption capacity and fast penetration speed, and alkaline impregnated materials are prone to pulverization and dust generation, and release large amounts of volatile organic compounds, which cannot meet the high cleanliness requirements of semiconductors; amino chelate type PS-DVB bimetallic resin: the preparation process contains serious residues of chloromethyl ether and long-chain polyamines, resulting in high TVOC in the finished product. The release exceeds the standard. The amino ligand is easily hydrolyzed and detached in a high-humidity acidic gas phase environment, and the risk of metal ion dissolution is high. Moreover, all existing patents are only applied to the liquid phase defluorination of water bodies, and there is no gas phase air filtration matching process and filter structure design. Conventional zirconium-loaded adsorption resin: using a single resin as a carrier, only impregnating a single metal zirconium oxide, has three major defects: (1) without lanthanum metal synergy, the selectivity of low-concentration gaseous fluoride is poor and the adsorption capacity is low; (2) only simply impregnating the loaded metal, without in-situ nano co-precipitation process, the metal oxide is easy to detach and dissolve; (3) all existing sulfonic acid zirconium-loaded resin patents limit the liquid phase working conditions of sewage treatment, and do not design hydrophilic pore expansion, low gas release purification, and single-layer filter matching process for the gas phase hydrolysis characteristics of HF and SiF4.
[0004] In summary, there is a need to develop a filter that can efficiently remove gaseous inorganic fluorine from the air, adapt to different operating conditions, balance low pressure drop and deep adsorption, have low gas release and low dust generation, be suitable for high humidity gas phase conditions in semiconductor applications, and be equipped with a dedicated modified resin filter. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a modified sulfonic acid resin for removing gaseous inorganic fluorine, its preparation method, application, and filter. Using a single sulfonic acid cation resin as a carrier, it eliminates high-overlapping processes such as chloromethylation and polyamine grafting. Through multiple steps including single resin substrate selection, sulfonic acid ion exchange anchoring of bimetals, in-situ co-precipitation of nano-solid solutions, hydrophilic pore expansion, and purification, it achieves efficient and long-lasting clean purification of gaseous inorganic fluorine.
[0006] The technical solution provided by this invention is as follows:
[0007] This invention provides a method for preparing a modified sulfonic acid resin for removing gaseous inorganic fluorine, comprising the following steps: Pretreated sulfonic acid-type strong acid cation exchange resin was added to a mixed solution containing zirconium salt and lanthanum salt to carry out an ion exchange reaction, resulting in a resin loaded with bimetallic ions. The resin loaded with bimetallic ions was dispersed in ultrapure water and then an alkaline solution was added, so that zirconium and lanthanum were precipitated in the resin channels in the form of zirconium / lanthanum metal oxide nanoparticles. After post-treatment, a resin loaded with nano-hydrated zirconium and lanthanum solid solution was obtained. The resin loaded with nano-hydrated zirconium lanthanum solid solution was added to the modification solution and subjected to hydrophilic pore-expanding modification under heating conditions. After post-treatment, it was subjected to segmented vacuum drying, cooling and sieving to obtain the modified sulfonic acid resin.
[0008] Furthermore, the sulfonic acid-type strong acid cation exchange resin is selected from gel-type sulfonic acid resin or macroporous sulfonic acid resin with a styrene-divinylbenzene copolymer backbone; the sulfonic acid-type strong acid cation exchange resin has an exchange capacity of 3.0~5.5 mmol / g based on dry resin; the macroporous sulfonic acid resin has a specific surface area of 20~80 m² / g, an average pore size of 5~50 nm, and a pore volume of 0.1~0.5 mL / g.
[0009] Furthermore, the pretreatment steps include: first, the sulfonic acid type strong acid cation exchange resin, which has been fully swollen after soaking in ultrapure water for 12-24 hours, is transformed by stirring with 3-7 wt% hydrochloric acid solution at a constant temperature for 1-3 hours, and then repeatedly rinsed with ultrapure water until the eluent is neutral; then, it is stirred with 3-7 wt% sodium hydroxide solution for 1-3 hours, and then repeatedly rinsed with ultrapure water until the eluent is neutral; fine powder with a particle size of less than 200 mesh is removed by airflow sieving, and finally, it is vacuum dried at 40-650℃ for later use.
[0010] Furthermore, the post-treatment involves repeatedly rinsing with ultrapure water until the eluent is neutral.
[0011] Furthermore, the zirconium salt is selected from one or more of zirconium oxychloride, zirconium nitrate, and zirconium sulfate; the lanthanum salt is selected from one or more of lanthanum nitrate and lanthanum chloride; the concentration of zirconium ions in the mixed solution is 0.05~0.5 mol / L, the concentration of lanthanum ions is 0.02~0.2 mol / L, and the molar ratio of zirconium ions to lanthanum ions is 1:0.2~1.
[0012] Furthermore, the temperature of the ion exchange reaction is 20~60℃, and the time is 2~24h; the mass-volume ratio of the pretreated sulfonic acid type strong acid cation exchange resin to the mixed solution is 1:5~20.
[0013] Furthermore, the alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, and ammonia water, and the concentration is 0.1~2.0 mol / L; the in-situ coprecipitation reaction is carried out at a temperature of 20~80℃ for 1~12h, and the pH of the reaction solution is maintained at 2~9; the zirconium / lanthanum metal oxide nanoparticles have a grain size of 2~20 nm and are anchored to the inner surface of the resin channels through Zr-OS and La-OS chemical bonds.
[0014] Furthermore, the modified solution is an aqueous solution of ethylene glycol monomethyl ether, and the volume fraction of the aqueous solution of ethylene glycol monomethyl ether is 10%~80%; the heating conditions are at a temperature of 40~100℃ and a time of 1~8h.
[0015] Furthermore, the segmented vacuum drying includes: drying at 40~65℃ for 1~3 hours, and then heating to 70~100℃ for 3~6 hours; the sieving process is to use airflow sieving to screen resin particles with a particle size of 40~60 mesh.
[0016] The present invention also provides a modified sulfonic acid resin for removing gaseous inorganic fluorine, which is prepared by the preparation method described above.
[0017] The present invention also provides a single-layer chemical filter, comprising a single-layer filter cloth composed of the modified sulfonic acid resin for removing gaseous inorganic fluoride as described above and a non-woven fabric.
[0018] The present invention also provides the application of the modified ion exchange resin or the single-layer chemical filter described above in the removal of gaseous inorganic fluorine in the air purification of semiconductor process workshops.
[0019] Beneficial effects
[0020] This invention utilizes Zr 4+ and La 3+ Synergistic loading and in-situ co-precipitation generated nano-hydrated zirconium lanthanum solid solutions, constructing a high-density fluoride ion-specific adsorption site on the resin framework. Hydrated zirconium oxide (HZO) and hydrated lanthanum oxide (HLO) have extremely strong coordination affinity for fluoride ions, and their fluoride removal mechanism is mainly ligand exchange—fluoride ions replace hydroxyl groups on the surface of metal oxides / hydroxides, forming stable internal coordination compounds. Zr-La bimetallic solid solutions have more abundant surface hydroxyl groups and stronger fluoride ion binding energy compared to single metal oxides. Testing showed that the modified resin of this invention has a saturated adsorption capacity of 20-40 mg / g for gaseous HF, which is 5-10 times higher than that of unmodified sulfonic acid resin. 4+ and La 3+ The selective coordination of fluoride ions enables the resin of this invention to react with HCl, SO2, and NO. xIt can preferentially adsorb HF even in coexisting acidic gases, with a selectivity coefficient (HF / HCl) ≥ 5.
[0021] This invention utilizes ion exchange to convert Zr 4+ and La 3+ Anchored to sulfonic acid sites, the active component undergoes in-situ co-precipitation to form a solid solution, resulting in Zr-OS and La-OS chemical bonds between the active component and the resin backbone. This chemical bonding method ensures the long-term stability of the active component under airflow scouring, with an active component shedding rate of <0.1%.
[0022] The ethylene glycol monomethyl ether hydrophilic hydroxyl pore-expanding modification of the present invention increases the pore size and specific surface area while introducing abundant hydroxyl and ether oxygen hydrophilic groups. After modification, the water contact angle of the resin is reduced to below 60°, significantly enhancing the surface affinity for polar HF molecules. At the same time, the enlarged pores reduce gas diffusion resistance, increasing the adsorption rate by 2 to 5 times.
[0023] The purification process of this invention effectively removes various volatile organic compounds remaining in the resin, with a TVOC content of <1ppb, avoiding secondary pollution of the cleanroom environment during the use of the filter, and meeting the stringent requirements of semiconductor manufacturing for chemical filters.
[0024] The single-layer nonwoven composite structure of this invention reduces the filter pressure and can be directly installed in existing FFU (Fan Filter Unit) systems; the high adsorption capacity and stable chemical bonding structure extend the filter's service life to 23 times that of traditional products.
[0025] The saturated resin of this invention can be completely regenerated through alkali washing-water washing-acidification. After 5 adsorption-desorption cycles, the fluorine adsorption capacity retention rate is ≥92%. The consumables can be reused, which greatly reduces the long-term operating cost of semiconductors. Attached Figure Description
[0026] Figure 1 These are comparison curves of the gas-phase HF adsorption and penetration performance of the examples and comparative examples;
[0027] Figure 2 It is a curve showing the change in the regeneration cycle capacity of the modified resin. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments thereof. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0029] This invention provides a method for preparing a modified sulfonic acid resin for removing gaseous inorganic fluorine, comprising the following steps: A pretreated sulfonic acid-type strong acid cation exchange resin is added to a mixed solution containing zirconium salt and lanthanum salt for ion exchange reaction to obtain a resin loaded with bimetallic ions. Specifically, a pretreated sulfonic acid-type strong acid cation exchange resin (H-type or Na-type) is added to a mixed solution containing zirconium salt and lanthanum salt, and through ion exchange reaction, Zr... 4+ and La 3+ Simultaneous exchange to the sulfonic acid sites of the resin backbone yields Zr-loaded... 4+ and La 3+ The resin.
[0030] A resin loaded with bimetallic ions was dispersed in ultrapure water, followed by the addition of an alkaline solution. This caused zirconium and lanthanum to precipitate as zirconium / lanthanum metal oxide nanoparticles within the resin channels. Post-treatment yielded a resin loaded with a nano-hydrated zirconium-lanthanum solid solution. Specifically, a resin loaded with Zr... 4+ and La 3+ The resin was dispersed in ultrapure water, and then an alkaline solution was added to allow the Zr in the channels to disperse. 4+ and La 3+ In-situ co-precipitation was performed to generate a nano-hydrated zirconium oxide-hydrated lanthanum oxide solid solution (Zr-La-HZO / HLO). The solution was then repeatedly washed with ultrapure water until the eluent was neutral, yielding a resin loaded with the nano-hydrated zirconium lanthanum solid solution.
[0031] The resin loaded with nano-sized hydrated zirconium lanthanum solid solution was added to a modification solution and subjected to hydrophilic pore-expanding modification under heating conditions. After post-treatment, it was then subjected to segmented vacuum drying, cooling, and sieving to obtain the modified sulfonic acid resin. Specifically, the resin loaded with nano-sized hydrated zirconium lanthanum solid solution was placed in a modification solution and treated under heating conditions. The modification solution was used to hydrophilically modify and moderately expand the pores of the resin. Subsequently, it was repeatedly rinsed with ultrapure water until the eluent was neutral. Then, it was subjected to segmented vacuum drying, cooling, and sieving to obtain the modified sulfonic acid resin.
[0032] In this embodiment, the sulfonic acid-type strong acid cation exchange resin is selected from gel-type sulfonic acid resin or macroporous sulfonic acid resin with a styrene-divinylbenzene copolymer backbone; the sulfonic acid-type strong acid cation exchange resin has an exchange capacity of 3.0~5.5 mmol / g based on dry resin; the macroporous sulfonic acid resin has a specific surface area of 20~80 m² / g, an average pore size of 5~50 nm, and a pore volume of 0.1~0.5 mL / g.
[0033] In this embodiment, the pretreatment steps include: first, the sulfonic acid type strong acid cation exchange resin, which has been fully swollen after soaking in ultrapure water for 12-24 hours, is first transformed by stirring with 3-7 wt% hydrochloric acid solution at a constant temperature for 1-3 hours, and then repeatedly rinsed with ultrapure water until the eluent is neutral; then, it is stirred with 3-7 wt% sodium hydroxide solution for 1-3 hours, and then repeatedly rinsed with ultrapure water until the eluent is neutral; fine powder with a particle size of less than 200 mesh is removed by airflow sieving, and finally, it is vacuum dried at 40-650℃ for later use.
[0034] In this embodiment, the zirconium salt is selected from one or more of zirconium oxychloride (ZrOCl2·8H2O), zirconium nitrate, and zirconium sulfate; the lanthanum salt is selected from one or more of lanthanum nitrate (La(NO3)3·6H2O) and lanthanum chloride; the concentration of zirconium ions in the mixed solution is 0.05~0.5 mol / L, the concentration of lanthanum ions is 0.02~0.2 mol / L, and the molar ratio of zirconium ions to lanthanum ions is 1:0.2~1.
[0035] In this embodiment, the temperature of the ion exchange reaction is 20~60℃, the time is 2~24h, and the mass-volume ratio of the pretreated sulfonic acid type strong acid cation exchange resin to the mixed solution is 1:5~20.
[0036] In this embodiment, the alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, and ammonia water, and the concentration is 0.1~2.0 mol / L; the temperature of the in-situ coprecipitation reaction is 20~80℃, and the time is 1~12h; the grain size of the zirconium / lanthanum metal oxide nanoparticles is 2~20 nm, and they are anchored to the inner surface of the resin channels through Zr-OS and La-OS chemical bonds.
[0037] In this embodiment, the modified solution is an aqueous solution of ethylene glycol monomethyl ether, with a volume fraction of 10% to 80%. The heating conditions are at a temperature of 40 to 100°C and a time of 1 to 8 hours. Specifically, the hydroxyl (-OH) and etheroxy groups of the aqueous solution of ethylene glycol monomethyl ether are used to hydrophilically modify and moderately expand the resin pores. After the hydrophilic pore-expanding modification, the specific surface area of the resin increases by 5% to 30%, the average pore size increases by 10% to 50%, and the water contact angle decreases to below 60°, significantly improving the affinity for polar HF molecules and the diffusion rate within the pores.
[0038] In this embodiment, the segmented vacuum drying includes: drying at 40~65℃ for 1~3 hours, and then heating to 70~100℃ for 3~6 hours to remove residual organic matter and volatile matter; the sieving process is to use airflow sieving to screen resin particles with a particle size of 40~60 mesh to reduce dust generation and meet the requirements of Class 1 cleanroom.
[0039] This invention also provides a modified sulfonic acid resin for removing gaseous inorganic fluorine, which is prepared by the method described above.
[0040] This invention also provides a single-layer chemical filter, comprising a single-layer filter cloth composed of the modified sulfonic acid resin for removing gaseous inorganic fluoride described above and a non-woven fabric.
[0041] In this embodiment, the nonwoven fabric is selected from one of polyester nonwoven fabric, polypropylene nonwoven fabric, and polyethylene nonwoven fabric, and the unit area mass is 20~100 g / m².
[0042] In this embodiment, the composite method is as follows: the modified sulfonic acid resin is uniformly dispersed in the form of powder or granules between nonwoven fibers and fixed by hot pressing, bonding or needle punching, with a resin loading of 400~800 g / m².
[0043] In this embodiment, the thickness of the single-layer chemical filter is 0.5~5 mm, the pressure drop is 10~50 Pa at a wind speed of 0.5 m / s, and the initial removal efficiency of HF is ≥90%.
[0044] This invention also provides the application of the modified ion exchange resin or the single-layer chemical filter described above in the removal of gaseous inorganic fluorine in the air purification of semiconductor process workshops.
[0045] Example 1: Macroporous zirconium-lanthanum bimetallic modified sulfonic acid resin
[0046] This invention provides a method for preparing a modified sulfonic acid resin for removing gaseous inorganic fluorine, the specific steps of which are as follows:
[0047] S1. Pretreatment: Immerse D001 resin in ultrapure water for 24 hours to allow it to fully swell; first, stir with 4wt% hydrochloric acid at a constant temperature for 2 hours to transform it, then rinse repeatedly with ultrapure water until the eluent is neutral; then stir with 4wt% NaOH for 2 hours, then rinse repeatedly with ultrapure water until the eluent is neutral; remove fine powder below 200 mesh by air sieving, and vacuum dry at 60℃ for later use.
[0048] S2. Prepare a mixed solution containing zirconium salt and lanthanum salt: Weigh 18.65g zirconium nitrate pentahydrate and 14.22g lanthanum nitrate hexahydrate and add them to 500mL of pure water. Stir well to obtain a mixed solution containing zirconium salt and lanthanum salt. The molar ratio of zirconium ions to lanthanum ions is 1:0.7 and the total metal ion concentration is 0.45mol / L.
[0049] S3, Ion Exchange Loaded Bimetal: Weigh 100 g of pretreated D001 resin and add it to a mixed solution containing zirconium salt and lanthanum salt. Stir at room temperature (20~40℃) at low speed (120 r / min) for 10 h, relying on the adsorption of Zr by sulfonic acid groups. 4 ⁺, La³⁺; filtration and separation yields resin loaded with bimetallic ions, discarding the upper layer containing free metal waste liquid.
[0050] S4. In-situ coprecipitation: The resin loaded with bimetallic ions was dispersed in ultrapure water, and 0.5 mol / L dilute ammonia was slowly added dropwise under stirring at room temperature (20~40℃). The pH was controlled stably at 4.5 by online pH monitoring. The mixture was stirred continuously for 5 hours to complete the in-situ formation of nano-hydrated zirconium lanthanum solid solution. The resin in the above solution was filtered out, and then repeatedly washed with ultrapure water until the eluent was neutral to obtain the resin loaded with nano-hydrated zirconium lanthanum solid solution.
[0051] S5. Hydrophilic pore-expanding modification: Prepare a 1.2 mol / L ethylene glycol monomethyl ether aqueous solution and adjust the pH of the system to 8.8 with 4 wt% NaOH; add the second mixed resin to the ethylene glycol monomethyl ether aqueous solution and stir at 58℃ for 4 h; then rinse repeatedly with ultrapure water until the eluent is neutral.
[0052] The specific surface area, pore size, and water contact angle of the resin before and after hydrophilic pore-expanding modification were determined using a physical adsorption instrument. After modification, the specific surface area increased by 34%, the average pore size increased by 52%, and the water contact angle decreased to below 60°, indicating that the hydrophilic pore-expanding modification significantly improved the hydrophilicity and pore structure of the resin.
[0053] S6. Purification: Segmented vacuum drying: The third mixed resin is kept at 60℃ for 2 hours to remove free water, and then heated to 85℃ for 3 hours to remove organic solvents and trace amounts of sulfate. After cooling, the resin is sieved by airflow to select uniform resin particles of 20~40 mesh to obtain the modified sulfonic acid resin.
[0054] The modified sulfonic acid resin obtained above is pressed into a single-layer filter cloth by needle punching process with non-woven fabric, which is then placed into a non-precipitated plastic frame and fitted with a sealing strip to obtain a single-layer chemical filter.
[0055] Single-layer chemical filter regeneration:
[0056] Regeneration mechanism: After the resin is saturated with adsorption, it is soaked and eluted with dilute sodium hydroxide or dilute ammonia solution. Fluoride ions are replaced by hydroxyl groups, and fluoride is removed from the metal active site. After washing with ultrapure water and acidification with dilute hydrochloric acid or sulfuric acid, the active sites of zirconium lanthanum hydrate oxide are restored, and it regains its fluoride adsorption capacity. The sulfonic acid framework has a strong binding force on zirconium lanthanum nanoparticles, and the metal loss during the regeneration process is extremely low. The adsorption capacity remains stable after multiple cycles.
[0057] To evaluate the actual effect of the above regeneration mechanism and the recycling performance of the material, referring to the ISO10121-2 standard, with 5 adsorption-desorption cycles as the evaluation period, the equilibrium adsorption capacity of the resin for fluoride ions after each cycle was measured, and the adsorption capacity retention rate was calculated to characterize the regeneration stability and reusability of the material.
[0058] like Figure 2 As shown, the modified resin of this invention exhibits an initial saturated adsorption capacity of 36 mg / g for gaseous HF. In Example 1, after five fluoride adsorption-desorption regeneration cycles, the fluoride adsorption capacity showed a slow, slight decrease without sudden decay. The capacity retention rate after the fifth cycle was approximately 93%, indicating good recovery capability of the adsorption performance. This result confirms that the zirconium-lanthanum nanosolid solution is firmly bound within the sulfonic acid-modified pores, resulting in extremely low metal ion dissolution during regeneration, and that the resin framework provides excellent confinement and anchoring for the nanoparticles. Therefore, this material can support long-term cyclic use, effectively reducing the replacement frequency and maintenance costs of gas filtration consumables in industries such as semiconductors.
[0059] To test the selective adsorption performance of the modified resin of this invention for HF under the coexistence of multiple acidic gases, a dynamic competitive adsorption experiment was conducted. The results showed that the resin exhibited selective adsorption performance for HF under the coexistence of HCl, SO2, and NO. x In the presence of coexisting acidic gases, the modified resin of this invention can still preferentially adsorb HF, with an HF / HCl selectivity coefficient ≥5. This result confirms that Zr supported on sulfonic acid resin... 4+ and La 3+ It exhibits strong selective coordination with fluoride ions, enabling specific capture of HF under conditions of competitive coexistence of various acidic gases, thereby endowing the modified resin of this invention with excellent selective adsorption advantages.
[0060] Example 2: Gel-modified sulfonic acid resin with zirconium lanthanum bimetallic resin
[0061] The other preparation steps and process parameters are the same as in Example 1, except that the sulfonic acid type strong acid cation exchange resin is N001.
[0062] The modified sulfonic acid resin obtained above is pressed into a single-layer filter cloth by needle punching process with non-woven fabric, which is then placed into a non-precipitated plastic frame and fitted with a sealing strip to obtain a single-layer chemical filter.
[0063] Comparative Example 1
[0064] The other preparation steps and process parameters are the same as in Example 1, except that only zirconium nitrate is added, and the total metal concentration is 0.45 mol / L.
[0065] Comparative Example 2
[0066] The other preparation steps and process parameters are the same as in Example 1, except that there is no hydrophilic pore-expanding modification step.
[0067] Comparative Example 3: Existing commercially available liquid-phase single zirconium simple impregnation with D001 resin (reference document CN103252220A)
[0068] The macroporous resin is simply converted to water washing with dilute hydrochloric acid, without airflow sieving to remove micropowder; it is simply impregnated with zirconium nitrate solution at room temperature for 2 hours, without lanthanum metal, in-situ co-precipitation, hydrophilic pore expansion, or segmented vacuum cleaning and devolatilization; it is simply dried once at 60℃. The modified resin and nonwoven fabric are pressed into a single layer of filter cloth through a needle punching process, packed into a non-precipitating plastic frame, and fitted with a sealing strip.
[0069] Dynamic breakthrough experiments were conducted to test the breakthrough performance of gas-phase HF adsorption. On a fixed-bed adsorption test bench, the resins from the examples and the comparative examples were filled into adsorption tubes. Under the same operating conditions (inlet HF concentration 10000 ppb, face velocity 0.7 m / s, relative humidity 50%), an HF-containing gas stream was continuously introduced. The change in outlet concentration over time was monitored online, and the breakthrough time when the adsorption efficiency of each material dropped to 70% was recorded. A breakthrough performance comparison curve was then plotted.
[0070] like Figure 1 As shown, the penetration time of Examples 1 and 2 is significantly better than that of the comparative examples, and the purification efficiency remains stable at over 70% during long-term operation. This result confirms that the combined effect of binary compounding, bimetallic synergy, and hydrophilic pore expansion can construct richer and more stable adsorption active centers within the sulfonic acid channels, thereby synergistically and significantly extending the gas-phase defluorination lifespan. This verifies the effectiveness of this composite modification strategy in improving the service life of materials.
[0071] The technical solutions disclosed and proposed in this invention have been described through examples, but the scope of protection of this patent is not limited thereto. It should be noted that for those skilled in the art, it is obvious that several improvements and modifications can be made based on the technical solutions and patent concept of this patent without departing from the content of this patent, and such improvements and modifications are considered to be within the scope of protection of this patent.
Claims
1. A method for preparing a modified sulfonic acid resin for removing gaseous inorganic fluorine, characterized in that, Includes the following steps: Pretreated sulfonic acid-type strong acid cation exchange resin was added to a mixed solution containing zirconium salt and lanthanum salt to carry out an ion exchange reaction, resulting in a resin loaded with bimetallic ions. The resin loaded with bimetallic ions was dispersed in ultrapure water and then an alkaline solution was added, so that zirconium and lanthanum were precipitated in the resin channels in the form of zirconium / lanthanum metal oxide nanoparticles. After post-treatment, a resin loaded with nano-hydrated zirconium and lanthanum solid solution was obtained. The resin loaded with nano-hydrated zirconium lanthanum solid solution was added to the modification solution and subjected to hydrophilic pore-expanding modification under heating conditions. After post-treatment, it was subjected to segmented vacuum drying, cooling and sieving to obtain the modified sulfonic acid resin.
2. The preparation method according to claim 1, characterized in that, The sulfonic acid-type strong acid cation exchange resin is selected from gel-type sulfonic acid resin or macroporous sulfonic acid resin with a styrene-divinylbenzene copolymer backbone; the sulfonic acid-type strong acid cation exchange resin has an exchange capacity of 3.0~5.5 mmol / g based on dry resin; the macroporous sulfonic acid resin has a specific surface area of 20~80 m² / g, an average pore size of 5~50 nm, and a pore volume of 0.1~0.5 mL / g.
3. The preparation method according to claim 1, characterized in that, The zirconium salt is selected from one or more of zirconium oxychloride, zirconium nitrate, and zirconium sulfate; the lanthanum salt is selected from one or more of lanthanum nitrate and lanthanum chloride; the concentration of zirconium ions in the mixed solution is 0.05~0.5 mol / L, the concentration of lanthanum ions is 0.02~0.2 mol / L, and the molar ratio of zirconium ions to lanthanum ions is 1:0.2~1.
4. The preparation method according to claim 1, characterized in that, The ion exchange reaction is carried out at a temperature of 20-60°C for 2-24 hours; the mass-to-volume ratio of the pretreated sulfonic acid-type strong acid cation exchange resin to the mixed solution is 1:5-20.
5. The preparation method according to claim 1, characterized in that, The alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, and ammonia water, and the concentration is 0.1~2.0 mol / L; the in-situ coprecipitation reaction is carried out at a temperature of 20~80℃ for 1~12h, and the pH of the reaction solution is maintained at 2~9; the zirconium / lanthanum metal oxide nanoparticles have a grain size of 2~20 nm and are anchored to the inner surface of the resin channels through Zr-OS and La-OS chemical bonds.
6. The preparation method according to claim 1, characterized in that, The modified solution is an aqueous solution of ethylene glycol monomethyl ether, and the volume fraction of the aqueous solution of ethylene glycol monomethyl ether is 10%~80%; the heating conditions are at a temperature of 40~100℃ and a time of 1~8h.
7. The preparation method according to claim 1, characterized in that, The segmented vacuum drying includes: drying at 40~65℃ for 1~3 hours, and then heating to 70~100℃ for 3~6 hours; the sieving process is to use airflow sieving to screen resin particles with a particle size of 40~60 mesh.
8. A modified sulfonic acid resin for removing gaseous inorganic fluorine, characterized in that, It is prepared by any one of claims 1 to 7.
9. A single-layer chemical filter, characterized in that, It includes a single-layer filter cloth composed of a modified sulfonic acid resin for removing gaseous inorganic fluoride as described in claim 8 and a nonwoven fabric.
10. The application of the modified ion exchange resin of claim 8 or the single-layer chemical filter of claim 9 in the removal of gaseous inorganic fluorine in the air purification of a semiconductor process workshop.
Citation Information
Patent Citations
Zirconium / macro-porous strong-acid styrene resin composite material and preparation thereof
CN103252220A